Will Prices Fall? - Moulton, H. G. (Journal of Political Economy, 1919)
The previous article' discussed the process by which the level of prices was raised and the quantity of circulating medium increased during the war. It is now our purpose to consider the possibilities of a fall in the general level of prices. In his recent analysis of post-war prices2 Professor Fisher observes that we have had a price revolution similar to that which followed the discovery of the New World and the appropriation of its great supplies of precious metals four hundred years ago. Professor Fisher bases his conclusion on the ground that there has been a permanent increase in the quantity of money multiplied by its velocity of circulation plus the quantity of credit currency multiplied by its velocity of circulation-in consequence of which the price quotient must remain permanently higher than it was before the war. With the general conclusion that we are not likely to witness any considerable fall in the general level of prices in the immediate future I find myself in substantial accord. Whether the price revolution will remain permanent, however, depends, I believe, upon factors that are not adequately treated by a mere statement of the equation of exchange of money and goods. An appreciation of the probable post-war trend of prices can best be gained by a consideration of the probable expenses of production of commodities. Let us consider first the relation between post-war prices and the volume of currency: It is generally assumed by quantity theorists that when bank currency has once been utilized it is practically certain to be used again-that when credit instruments have once entered the channels of circulation they remain there indefinitely as price-determining factors. This assumption, I